Students’ Perceptions and Ethical Use of ChatGPT in Completing English Assignments: A Mixed-Method Study - Yetty Yetty; Firmansyah Firmansyah; Susana R Bahara; Nadia Idris; Hordi Glen Gogaho (PT. Global Research Collaboration, 2026)
This study aimed to explore students’ perceptions and ethical use of ChatGPT in completing English assignments. The research employed an explanatory sequential mixed-method design that combined quantitative and qualitative approaches. The participants were 68 students from the English Education Study Program at Khairun University, selected through purposive sampling. Data were collected through questionnaires and semi-structured interviews. Quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed descriptively to enrich the quantitative findings. The results showed that students generally had positive perceptions of ChatGPT, with an overall mean score of 3.66 across seven dimensions: input, process, output, outcome, efficiency, academic ethics, and satisfaction. Students considered ChatGPT a useful learning tool, mainly for searching references and generating ideas. They reported that ChatGPT improved grammar, expanded vocabulary, enhanced assignment quality, and increased motivation and critical thinking. Participants also valued its efficiency in saving time and facilitating task completion. Furthermore, they demonstrated ethical awareness by reviewing, revising, and paraphrasing AI-generated content and recognizing the risk of overreliance. Overall, ChatGPT can serve as an effective learning support tool when used critically, ethically, and responsibly in higher education, particularly for English language learning in Eastern Indonesia.